Blood pressure management and stroke prevention - Silverman, Isaac E. (Visual guide for clinicians., 2012)
This guide provides a visual overview of the basic concepts clinicians managing patients with hypertension should understand about ischemic stroke. This title will be a useful reference for doctors treating hypertension in hospital and primary care.